The Need To Study The Categories Of Words In The Morphology Of The English Language - Abduvaliyeva Shakhnoza Abduvaliyevna (Zien Journals, 2024)
Words are divided into certain categories, primarily according to the concepts they mean. Words in a language differ from each other not only in the specific meanings they mean, but also in grammatical features. The largest groups of words that differ in common semantic and grammatical features are called word categories
Keywords: Linguistics; categories of words; morphology